Test investigation and direct strength method on cold-formed steel compression members with web holes of different widths. (1st December 2022) - Zhao, Jinyou; Liu, Jiaqi; Yu, Cheng; Zhang, Wenying
Highlights: Tests on the compressive behaviors of cold-formed steel (CFS) compression members with web holes of different widths. The finite element (FE) analyses on CFS compression members with different parameters. The hole impact coefficient formulas on the proportional relationships between the ultimate bearing capacities of CFS compression members with web holes and that without web holes were developed. The simpler DSM formulas of CFS compression members with web holes were proposed, in which the elastic critical buckling stress of CFS compression members with web holes was not necessary to be calculated. Abstract: This paper presents a series of test investigations and finite element (FE) analyses on the compressive behaviors of cold-formed steel (CFS) compression members with web holes of different widths and the corresponding direct strength design method is proposed. In the test investigations, a total of twenty specimens were tested under axial compression loading with five different hole width-to-web width ratios of 0, 0.2, 0.4, 0.6, and 0.8. It is shown that the local buckling deformations for specimens with web holes occur in the vicinity of web holes and decrease as the hole widens. For the axial capacities of specimens, they are decreased by 11.7% on average with the increase of hole width-to-web width ratio from 0 to 0.4 while they are decreased by 31.5% on average with the increase of hole width-to-web width ratio from 0.4 to 0.8. In the FE studies, the FE models for CFS compression members with web holes of different widths were developed using the ANSYS program. The simulation results show that the compressive behaviours obtained from FE analyses are in good agreement with test results. Then, combined with test data, a total of 412 FE parametric analyses were conducted to predict the proportional relationships between the axial capacities of compression members with web holes and those without web holes, and the hole impact coefficient formulas were correspondingly derived which differ from the previous researcher's contribution. Based on the hole impact coefficient formulas and the direct strength method (DSM) of CFS compression members without web holes in AISI S100-2016, the DSM formulas of CFS compression members with web holes were developed, in which the elastic critical buckling stress of CFS compression members with web holes was not necessary to be calculated.